Strategy for development of counseling guidelines in basic schools in dealing with millennial 4.0 era - Thoyyibah, Idzaa Zubdatun; Sari, Apriliani Indah (Universitas Sebelas Maret, 2019)
In this era of guidance and counseling services in primary schools requires a better strategy. Therefore, this paper aims to describe the strategy of guidance and counseling in schools to deal with millennial generation 4.0. Guidance and counseling services that have received updates or innovations in their implementation certainly can overcome the problems that are being faced by students. This research uses the literature study method and the data collected is obtained from journals that are in accordance with this research. Literature sources obtained from journals, research, and books. This research includes the process of identifying theories that are prepared systematically, finding literature, and analyzing documents that contain information that is relevant to the research topic. The results of this study are in the form of strategies for developing guidance and counseling in elementary schools to deal with the milineal 4.0 era.